Capitalization, regulation and the poor: Access to basic services in Bolivia - Gover Barja; Miguel Urquiola (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
This paper analyses the privatization of utilities in Bolivia, detailing the particularities of the capitalization mechanism which was used for this purpose. The analysis suggests that capitalization and regulation, and the liberalization of the utilities sector more generally, succeeded in attracting foreign investment, thus fulfilling one of the central goals of the reforms of this sector. Foreign investment made possible the increase in access to basic services in urban areas, although access in rural areas still remains very low. In terms of connection, service expansion in the urban areas did not bypass the poor. On the contrary, in some cases, access improvements appear to have been particularly beneficial to low-income households. Some reform-related price increases did have adverse welfare effects. Nevertheless, the findings in this area are affected by data limitations, and in any case do not seem to outweigh the benefits brought about by greater access. – privatization ; regulation ; utilities ; poverty
Keywords: L100; L500; L900; 330; Versorgungswirtschaft; Privatisierung; Regulierung; Bolivien